Disfunción tiroidea subclínica en población adulta costarricense - Guevara Sánchez, Oscar (2015)
Introduction. Subclinical thyroid dysfunction is a common disorder which may represent the early stage of a thyroid disease. Objective. To determine the prevalence of subclinical thyroid dysfunction in an adult population. Design. Cross-sectional descriptive study. Setting. Urban area of Costa Rica. Participants. Costa Rica urban area adult population. Interventions. Family history of hypertension, fractures and diabetes mellitus, thyroid or cardiovascular disease and obesity were investigated in 297 individuals of both genders aged 30 to 87 years. TSH, total T4 and T3, free T4 fraction, glucose and lipid profile were analyzed. Results. Subclinical thyroid dysfunction was found in 15.7% of participants including subclinical hyperthyroidism in 3.9% and subclinical hypothyroidism in 11.8%, 3 times more prevalent in women than in men. About 50% of all participants were overweight or obese, regardless of thyroid status. Conclusions. In Costa Rica there is no policy of early identification or management of patients with subclinical thyroid dysfunction.